ANALISIS SALURAN PEMASARAN DAN PENGENDALIAN MUTU KOMODITAS PERIKANAN MELALUI OPTIMALISASI COLD STORAGE PPI SELILI: Analysis of Marketing Channels and Quality Control of Fishery Commodities Through the Optimization of Cold Storage at Selili Fish Landing Base - Nur Indah Pratiwi; Syakira Permadani Machdi; Andi Muttia Yunita Mentari Sayuti; Sitti Fakhriyyah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2026)
This study aims to analyze the marketing channels of fishery commodities, examine the quality control of fishery products, and evaluate the utilization of cold storage facilities at the Selili Fish Landing Site (PPI Selili) in Samarinda City, Indonesia.. The research employed a descriptive survey method using both quantitative and qualitative approaches through observation, interviews, and primary data collection. The results showed that there are three marketing channels, namely Fishermen–PPI Selili–Consumers, Fishermen–Collectors–PPI Selili–Consumers, and Fishermen–Collectors–PPI Selili–Retailers–Consumers. The highest marketing margin was obtained by retailers, while the total marketing margin from fishermen to retailers ranged from IDR 3,000/kg to IDR 29,000/kg. The findings also indicate that the utilization of cold storage facilities at PPI Selili still requires improvement to better support the maintenance of fishery commodity quality. Therefore, optimizing cold storage facilities is expected to help maintain fish freshness, extend shelf life, and improve the efficiency of the fisheries supply chain in the region.